PENGARUH LOAN TO DEPOSIT RATIO (LDR) TERHADAP EARNING PER SHARE (EPS) DI PT BNI Tbk. PERIODE 2008-2017 - Adhianto, R. Deden (Jurnal E-Bis (Ekonomi-Bisnis), 2019)
This research aims to know how much the effetc of loan to deposit ratio (LDR) against earning per share (EPS) at PT Bank BNI Tbk. The method that is used in this research is quantitative method. By taking samples of research from 2008 to 2017. Based on the analysis of the data, it indicates that the loan to deposit ratio has strong relation with earning per share as of the value of pearson correlation coefficient is 0,902%. Loan to deposit ratio also has positive and significan effect on the earning per share with a coefficient of determination amounted to 81,36 % and T test results showes t calculate>t table amounted to (5,898>2,360) confidence level (0,05) with degrees of freedom 8 therefore Ho rejected and H1 accepted. The suggestion given to maintain level the BI’ LDR standar, to avoid problem decrease in CAR standar and result high EP.